Iatrogenic bleeding during flexible bronchoscopy: risk factors, prophylactic measures and management. Issue 2 (21st June 2017) - Bernasconi, Maurizio; Koegelenberg, Coenraad F.N.; Koutsokera, Angela; Ogna, Adam; Casutt, Alessio; Nicod, Laurent; Lovis, Alban
Significant iatrogenic bleeding during flexible bronchoscopy is fortunately rare and usually self-limiting. Life-threatening bleeding, however, can occur, especially after conventional or cryoprobe-assisted transbronchial biopsy. The aim of this review is to provide the practising pulmonologist with a concise overview of the incidence, severity and risk factors for bleeding, to provide sensible advice on prophylactic measures and to suggest a plan of action in the case of significant bleeding. Bronchoscopy units should have a standardised approach and plan of action in the case of life-threatening haemorrhage. Wedging the bronchoscope in the bleeding segment, turning the patient in an anti-Trendelenburg position and onto the side in order for the bleeding lung to be in the dependent position, installing vasoconstrictors and using a tamponade balloon early are the recommended first-line strategies. Involving a resuscitation team should be considered early in the case of massive bleeding, desaturation and haemodynamic instability. Iatrogenic bleeding during flexible bronchoscopy http://ow.ly/w9Fy30bsoe5